Redox modification of proteins as essential mediators of CNS autophagy and mitophagy. Issue 15 (15th June 2013) - Lizama-Manibusan, Britney; McLaughlin, BethAnn
Abstract : Production of cellular reactive oxygen species (ROS) is typically associated with protein and DNA damage, toxicity, and death. However, ROS are also essential regulators of signaling and work in concert with redox‐sensitive proteins to regulate cell homeostasis during stress. In this review, we focus on the redox regulation of mitophagy, a process that contributes to energetic tone as well as mitochondrial form and function. Mitophagy has been increasingly implicated in diseases including Parkinson's, Amyotrophic Lateral Sclerosis, and cancer. Although these disease states employ different genetic mutations, they share the common factors of redox dysregulation and autophagic signaling. This review highlights key redox sensitive signaling molecules which can enhance neuronal survival by promoting temporally and spatially controlled autophagic signaling and mitophagy.